The Effect of Working from Home on Employee Performance with Organizational Commitment as a Moderating Variable - Dwi Peni; Zainnur M. Rusdi (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Working from home can improve employee performance but also pose challenges for employees. Employees who work from home will avoid distractions at the office, have a better work-life balance and avoid office politics. But on the other hand, working from home can also increase stress in employees due to the increase in video conferences compared to face-to-face meetings felt by employees, so that high organizational commitment is needed so that employees can continue to face existing challenges and maintain their performance. This study aims to determine the effect of working from home on employee performance with organizational commitment as a moderating variable in Indonesia. The method used in this research is quantitative method with purposive sampling technique. The total respondents in this study were 240 respondents from all over Indonesia. For hypothesis testing, the moderated regression test using Moderated Regression Analysis (MRA) by Hayes and t test were used. The results showed that working from home has a positive and significant effect on employee performance. Other results show that organizational commitment does not moderate the positive effect of working from home on employee performance. Therefore, companies can create monthly evaluation activities, performance support systems and involve employees in every process of formulating company policies. Therefore, companies can create monthly evaluation activities, performance support systems and involve employees in every process of formulating company policies.